ӘР ТҮРЛІ ПІШІНДЕГІ ТОЗАҢДЫ БӨЛШЕКТЕРДІҢ МЕЗОСФЕРА БИІКТІКТЕРІНДЕ ЗАРЯДТАЛУЫН САЛЫСТЫРУ - Шиникулова, Гульнур; Рүстемова , Қарашаш; Мәжит, Жамиля; Алдибекова , Айткүл; Шынықұлова , Нұргүл (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2025)
Abstract. This work considers the charging process of dust particles depending on their shape when interacting with plasma particles of O, O₂, O₃, and OH gases, among the many surrounding gases at mesosphere altitudes. For the purpose of comparison with spherical particles, the dependence of their charge on electron temperature was determined, taking into account the capacitances of cylindrical and disc-shaped particles. Calculations were performed for the ionospheric plasma at an altitude of 85 km, with a temperature of 150 K, electron and ion concentrations of 1010 м-3 and an ion frequency of 105 с-1. The OML theory was used to model the charging of dust particles. The calculation results showed that the shape of the dust particles in the mesospheric plasma affects the magnitude of the charge: spherical particles have the largest negative charge, cylindrical particles have a somewhat smaller charge, and disc-shaped particles have the smallest charge.